The Power of Illusion. Disgust and Representability in Moses Mendelssohn’s Aesthetics - Feloj, Serena (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In the context of the emergence of aesthetics as an autonomous discipline in mid-eighteenth-century Germany, Moses Mendelssohn was one of the leading voices in the development of a new theory of sentiments and representation. In this context, Mendelssohn understood the need to delineate the limits of aesthetic representation and addressed the issue through an in-depth study of sentiments. In this article, I propose a study of the category of disgust in Mendelssohn’s aesthetics, starting from his theory of aesthetic illusion. Disgust is, in fact, a feeling that cannot be reduced to the illusion created by the work of art but always refers to reality. To this end, I will refer mainly to the 82nd Literaturbrief, in which Mendelssohn expounds his study of disgust, and secondly to the Rhapsody as a text that reveals the need to deepen the theory of aesthetic illusion in light of the limits indicated through disgust. Finally, an aesthetic paradigm will emerge, which is also relevant to the contemporary debate on the possibilities of aesthetic representation